The open source alternative : understanding risks and leveraging opportunities - Meeker, Heather J., 1959- (Hoboken, N.J. : Wiley & Sons, 2008)
A user manual for understanding and deployment of open source software licensing in business, this book explains and analyzes open source licensing issues, and gives practical suggestions on how to deal with open source licensing in a business context. It is written for lawyers and businesspeople alike.
Free software and open source -- Common open source licenses and their structure -- Due diligence, license proliferation, and compatibility -- Audits and compliance initiatives -- Notice requirements -- Patents and open source -- Trademarks and open source -- Open source and open standards -- Developing a corporate open source policy -- Open source code releases -- Technical background : operating system kernels, user space, and elements of programming -- Enforcement of open source licenses -- The border dispute of GPL2 -- License or contract? -- Defining distribution -- Open source in mergers and acquisitions and other transactions -- GPL version 3.0 -- LGPL version 3.0.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Open source software -- Law and legislation; Computer programs -- Patents; Copyright -- Computer programs; Computer software industry -- Licenses; Free computer software -- Law and legislation; Logiciels -- Brevets d'invention.; Droit d'auteur -- Logiciels; LAW -- Business & Financial; LAW -- Intellectual Property -- General; Computer programs; Computer software industry -- Licenses; Copyright -- Computer programs; Free computer software -- Law and legislation; Open source software -- Law and legislation; Patents